Commonly used diagnostic label, classes, domain, and formulation among nursing students in Ibadan, Oyo State Nigeria - Iyanuoluwa O. Ojo; Elizabeth O. Kazeem; Olufemi O. Oyediran; Timothy O. Oladosu; Adenike A. Olaogun; Prisca O. Adejumo (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: In order to select nursing actions that will produce the desired results, a nursing diagnosis is crucial. Despite this, it can be challenging for nursing students to recognize and create precise nursing diagnostic labels that are particular to a patient's situation. The study's objectives are to identify the diagnostic labels, classes, and domains that are frequently formulated by nursing students. MATERIALS AND METHODS: A descriptive cross-sectional methodology and a self-developed questionnaire were utilized to gather information from 120 nursing students who were chosen using a simple random sampling technique. Descriptive and inferential (Chi-square) statistics were used to analyze the data. The 0.05 P- value was chosen. RESULTS: The respondent's average age is 23 ± 21.4 years. The majority of respondents (94.2%) concurred that greater exposure to clinical settings, case discussion methods (92.5%), as well as group case studies (90.8%) strategy, can all improve the creation of precise diagnostic labels. Additionally, the deficient fluid volume diagnostic label is the one that is most usually utilized (78.3%). Overall results show that the diagnostic labels that are used the most frequently are those for domains 4 (Activity/Rest) and 11 (Safety/Protection). There was no relationship (P = 0.061) between the commonly used diagnostic label and the chosen schools. CONCLUSION: The study offered empirical data on the most used diagnostic labels and domains. Therefore, it will be important that nursing students involve critical reasoning skills as well as familiarize themselves with other significant domains and classes that are useful in the patient's care.